Asymmetrical proliferative pattern loss during malignant transformation of the oral mucosa. (12th February 2014) - González‐Moles, M. A.; Plaza‐Campillo, J.; Ruiz‐Ávila, I.; Herrera, P.; Bravo, M.; Gil‐Montoya, J. A.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to study the loss of asymmetrical proliferation in oral tumorigenesis. Materials and methods Samples: 92 oral squamous cell carcinomas (OSCC) with associated non‐tumor epithelia (NTE). NTE and tumor were classified as distant from or close to the invasion point. Immunohistochemistry was performed using Mib‐1 antibody. Ki‐67 was assessed in basal, parabasal layer, medium and upper third, counting total and positive cells. Proliferative patterns were classified according to the ki‐67 expression: 1 = expression in parabasal layers of well‐differentiated tumor nest (WDTN); 2 = expression in parabasal and basal layers of WDTN; 3 = ki‐67 expression in <20% cells in tumor tissue without WDTN; 4 = ki‐67 expression in ≥20% of cells in tumor tissue without WDTN; and 5 = ki‐67 expression exclusively found in basal layers of WDTN. Results Ki‐67 expression was highest in parabasal layers of both close and distant NTE (39.7 ± 27.6 and 30.1 ± 20) and was also elevated in the close (43.4 ± 21.3) and distant (48.8 ± 21.9) tumor tissue samples. Close tumors largely corresponded to proliferation patterns 2 and 4, while distant tumors generally followed pattern 4. Of the 92 close NTE samples, 23 showed reduced basal proliferation with increased parabasal proliferation. Tumors derived from these epithelia followed patterns 2 (52%, 12/23 cases) or 4 (30.4%, 7/23 cases). Parabasal proliferation in distant NTE was significantly increased in patients with multiple vs. single tumors (36.7% vs. 25.4%; P = 0.032). Conclusion The change from asymmetrical to symmetrical division appears to be an oncogenic mechanism in oral carcinogenesis.